Britain and ASEAN : Strengthening Ties Post-Brexit - Wightman, Scott (2018)
The UK makes a tangible and significant contribution to the security and prosperity of Southeast Asia, and to strengthening and supporting ASEAN, and the Rules Based International System (RBIS) it seeks to uphold. This contribution will be even stronger after the UK leaves the European Union.